Patologi sosial - Kartini Kartono (Rajawali, 1988)
tr, jil.1=c.1-3/oen, Jil.1=c.4;Jil. 2=c.1/ir,jil.1,c.5/ir, jil.1,c.6/ir,jil.3,c.1-2/tr, jil.2=c.2-3; jil.1=c.7-10/tr, jil.1=c.11/en, jl.1=c.12/en, c.13/ws.jl.3.c.3-7